2017
DOI: 10.1016/j.scitotenv.2017.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Can brook trout survive climate change in large rivers? If it rains

Abstract: We provide an assessment of thermal characteristics and climate change vulnerability for brook trout (Salvelinus fontinalis) habitats in the upper Shavers Fork sub-watershed, West Virginia. Spatial and temporal (2001-2015) variability in observed summer (6/1-8/31) stream temperatures was quantified in 23 (9 tributary, 14 main-stem) reaches. We developed a mixed effects model to predict site-specific mean daily stream temperature from air temperature and discharge and coupled this model with a hydrologic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…We observed the greatest decrease in warming downstream of major tributaries, where channel narrowing increased transport and decreased warming of cold‐water inputs. These results add to an increasing number of studies documenting the importance of network topology and cold‐water inputs on the thermal regimes of this (Merriam et al ) and other larger‐river systems (Kiffney et al ; Rice et al ; Ebersole et al ; Fullerton et al ). However, ours is the first study to consider and document thermal benefits of in‐stream restoration within the context of major tributary inputs and associated thermal discontinuities and highlights the need to account for these complexities to maximize and realize potential benefits of restoration.…”
Section: Discussionsupporting
confidence: 64%
“…We observed the greatest decrease in warming downstream of major tributaries, where channel narrowing increased transport and decreased warming of cold‐water inputs. These results add to an increasing number of studies documenting the importance of network topology and cold‐water inputs on the thermal regimes of this (Merriam et al ) and other larger‐river systems (Kiffney et al ; Rice et al ; Ebersole et al ; Fullerton et al ). However, ours is the first study to consider and document thermal benefits of in‐stream restoration within the context of major tributary inputs and associated thermal discontinuities and highlights the need to account for these complexities to maximize and realize potential benefits of restoration.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the effects of summer conditions have been studied extensively; abundance has consistently been found to be positively correlated with summer streamflow and negatively correlated with summer temperature (Nislow et al 2004, Xu et al 2010a, Warren et al 2012, Letcher et al 2015b, Kovach et al 2016, Merriam et al 2017). Furthermore, the effects of summer conditions have been studied extensively; abundance has consistently been found to be positively correlated with summer streamflow and negatively correlated with summer temperature (Nislow et al 2004, Xu et al 2010a, Warren et al 2012, Letcher et al 2015b, Kovach et al 2016, Merriam et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…First, sub-lethal thermal physiology could increase or decrease individual energy budgets depending on seasonal changes in growing-degree days and prey availability (Ries and Perry 1995). Altered flow regimes may also affect fishes indirectly by altering air-water temperature relationships and subsequent thermal habitat conditions (Merriam et al 2017). Alternatively, warming at cold-edge limits could enhance growth and recruitment, allowing upslope range expansions (Lawrence et al 2015).…”
Section: Future Shifts In Elevation Limitsmentioning
confidence: 99%
“…Indeed, our inability to consistently model water temperatures from air temperature and landscape features using different statistical algorithms contributed the most uncertainty to our projections of warming tolerance. For example, Merriam et al (2017) identified low flows in combination with high air temperatures contributing to thermal stress of Brook Trout in central Appalachian streams. This statistical property is not explicitly incorporated into our stochastic air temperature simulations, meaning that our estimation of T extreme events could be conservative.…”
Section: Future Shifts In Elevation Limitsmentioning
confidence: 99%